Cost‐benefit analysis of using biochar to improve cereals agriculture. Issue 4 (29th April 2014) - Dickinson, Dane; Balduccio, Ludovico; Buysse, Jeroen; Ronsse, Frederik; van Huylenbroeck, Guido; Prins, Wolter
Abstract Biochar has received considerable scientific attention in the past decade as a possible method for carbon storage and increasing agricultural yields. Despite this promise, however, economic assessments of biochar are yet to definitively establish the value of the technology, primarily due to discrepancy between observed short‐term agronomic benefits and expectations of biochar as a lasting soil improver. This study investigated the economic value of biochar as an agricultural technology for long‐term improvement of arable farming. From presently available field trial data, the costs and benefits of using biochar technology to enhance cereals agriculture were evaluated in two generalized geo‐economic agricultural scenarios: North‐Western Europe (NWE) and Sub‐Saharan Africa (SSA). Cost models were developed to estimate the total cost of biochar from initial biomass feedstock acquisition to final soil application for each agricultural setting. Benefits of biochar application were estimated by statistical meta‐analysis of crop yield data from published biochar field trials to find the increase in cereal grain yield attributable to biochar application for both NWE (+0.07 to +0.28 t ha−1 yr−1) and SSA (+0.18 to +1.00 t ha−1 yr−1). The grain yield improvement from a one‐time biochar application was assumed to persist without decay for an independently varying time period, and the increase in grain production then monetised using projected future commodity prices. The Net Present Value (NPV) of applying biochar was then calculated by setting present total costs against present total benefits as a function of biochar performance longevity. Biochar application was found to carry a positive NPV for cereal cropping in SSA in several scenarios where the duration of the biochar yield effect was assumed to extend 30 years into the future. Conversely, NWE biochar scenarios were all found to have negative NPVs even when the benefits time span was indefinitely stretched.